Neutrophil Extracellular Traps in Periodontitis: A Web of Intrigue. (January 2016) - White, P.C.; Chicca, I.J.; Cooper, P.R.; Milward, M.R.; Chapple, I.L.C.
Neutrophil extracellular traps (NETs) represent a novel paradigm in neutrophil-mediated immunity. NETs are believed to constitute a highly conserved antimicrobial strategy comprising decondensed nuclear DNA and associated histones that are extruded into the extracellular space. Associated with the web-like strands of DNA is an array of antimicrobial peptides (AMPs), which facilitate the extracellular destruction of microorganisms that become entrapped within the NETs. NETs can be released by cells that remain viable or following a unique form of programmed cell death known as NETosis, which is dependent on the production of reactive oxygen species (ROS) and the decondensing of the nuclear DNA catalyzed by peptidyl arginine deiminase-4. NETs are produced in response to a range of pathogens, including bacteria, viruses, fungi, and protozoa, as well as host-derived mediators. NET release is, however, not without cost, as the concomitant release of cytotoxic molecules can also cause host tissue damage. This is evidenced by a number of immune-mediated diseases, in which excess or dysfunctional NET production, bacterial NET evasion, and decreased NET removal are associated with disease pathogenesis. Periodontitis is the most prevalent infectious-inflammatory disease of humans, characterized by a dysregulated neutrophilic response to specific bacterial species within the subgingival plaque biofilm. Neutrophils are the predominant inflammatory cell involved in periodontitis and have previously been found to exhibit hyperactivity and hyperreactivity in terms of ROS production in chronic periodontitis patients. However, the contribution of ROS-dependent NET formation to periodontal health or disease remains unclear. In this focused review, we discuss the mechanisms, stimuli, and requirements for NET production; the ability of NET-DNA and NET-associated AMPs to entrap and kill pathogens; and the potential immunogenicity of NETs in disease. We also speculate on the potential role of NETs in the pathogenesis of periodontitis.